Pengaruh Kebugaran Jasmani dan Gaya Hidup Sehat Terhadap Kinerja Pasukan Katak TNI-AL - Lucya Febrianti; Iwan Hermawan; Mansur Jauhari (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to analyze the effect of physical fitness and healthy lifestyle on the performance of Indonesian Navy Frogman personnel. The study employed a quantitative causal-associative approach using path analysis and regression with SPSS. The research sample consisted of 20 active Frogman personnel from Indonesian Navy Fleet Command 1 selected through purposive sampling. Physical fitness data were obtained from official Navy physical readiness test documents, including the 12-minute run, pull up, sit up, push up, and shuttle run. Healthy lifestyle data were collected using a Likert-scale questionnaire, while performance data were obtained from direct supervisor assessments. The results showed that physical fitness did not significantly affect personnel performance, with a significance value of 0.363 > 0.05. Healthy lifestyle also did not significantly affect personnel performance, with a significance value of 0.094 > 0.05. Simultaneously, physical fitness and healthy lifestyle did not significantly affect Frogman personnel performance, with an F value of 1.187 and a significance value of 0.346 > 0.05. The coefficient of determination was 0.182, indicating that both variables explained only 18.2% of the variation in performance, while 81.8% was influenced by other factors. The study concludes that physical fitness and healthy lifestyle were not dominant factors affecting personnel performance in the research sample; therefore, other factors such as operational experience, work environment, training intensity, motivation, and rest patterns should be considered in future studies. Keywords: Healthy Lifestyle, Physical Fitness, Personnel Performance, Frogman, Indonesian Navy.